The Picture And Picture Learning Model To Improve The Thinking System Of Grade III Elementary School Students In The Skills Of Writing Narrative Texts - Rubi'ah, Chitra; Heryani, Rina; Saputri, Aprilia Eki (International Conference on Elementary Education, 2025)
Literacy is skills or ability somebody in understand something with reading and writing literacy is foundation important in mastery various skills speaking, including skills writing. Participants educate school base still experience constraint in expressing ideas, understanding story themes, and composingflow in a coherent manner. Purpose from study this is do analysis to effectiveness model Picture and Picture to improve system thinking participant educate class three school base in skills write text narrative approach this help participant educate understand connection cause and effect and integration between events in the story. The method used in study this is quantitative with design pre-experiment one group pretest - posttest on 25 participants educated. Data obtained from the writing test narrative before and after treatment, then the result analyzed use paired sample t-test and N - Gain test. Based on results research, obtained proof existence significant improvements to the system thinking and skills write narrative after its implementation model Picture and Picture with mark significance 0.001 < 0.05 and N- Gain by 44.26% ( category medium). The results show that use of the Picture and Picture model capable increase systems thinking and skills write text narrative to participants educate class three school base.